A five-year development plan for the Asean Regional Centre for Biodiversity Conservation (ARCBC) Library - Annex, Quezon City a proposal - Garcia, Glenn E.; Faderon, Rosalie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
This study focused on the formulation of a five-year development plan for the ASEAN Regional Centre for Biodiversity Conservation (ARCBC) Library Annex, Quezon City. It presented the present condition of the library in terms of personnel, collection, facilities, services, and funding. A survey was conducted to evaluate the library and elicit the information needs of the ARCBC Co-directors and annex staffs.
The survey was limited to the ARCBC Co-directors and staff of the annex office since they are the most frequent users of the library. Of the 12 respondents, 7 (58.33 percent) are male and 5 (41.66 percent) are female. Each respondent was given a questionnaire, each reflecting his/her profile, evaluation of the library, and information needs.
The data gathered revealed that: 1) the ARCBC Library Annex has a substandard collection - some materials are either missing or outdated and has multiple copies of different materials, thus making the library cramped; 2) library service is hampered due to limited library budget and manpower; and 3) the library should prioritize in re-organizing its materials such as physical arrangement, shelving, and re-accessioning before planning for new library services. The Gantt chart outlines the performance targets and activities to be taken by the ARCBC Library-Annex, Quezon City for a period of five years. The focus would be to re-arrange the collections of the library, re-accession the collection, acquire new materials, promote new services using the current awareness service program and develop and conduct library training programs.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: ASEAN Regional Centre for Biodiversity Conservation (ARCBC) Library -- Evaluation